2005
DOI: 10.1136/jmg.2005.037747
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype of triploid embryos

Abstract: The phenotypes of triploid fetuses and placentae are now well established and known to correlate with parental origin of the extra haploid set of chromosomes. In fetuses, it is not clear whether there is a direct parent of origin effect on the fetus itself or if the phenotypes are the result of growth differences influenced by abnormalities in growth and function of the placenta. Examining the phenotype of triploid embryos at an earlier stage in gestation, when the placenta effects may be less pronounced, coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
55
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 19 publications
5
55
0
1
Order By: Relevance
“…In addition, because the unbalanced translocations were associated with congenital malformations and were inherited from a phenotypically normal balanced translocation carrier, it is likely that the extra copy of the triplicated 9 McFadden et al, 10,11 Baumer et al, 12 Daniel et al 13 and Kajii et al 14 Triploidy, trisomy and choice of active X BR Migeon et al segment was expressed. Direct duplications in males and females were also mapped but were not used for exclusions, as both copies are on the same chromosome and might function as one copy rather than two and might be subject to position effects.…”
Section: Inactivation Studiesmentioning
confidence: 99%
“…In addition, because the unbalanced translocations were associated with congenital malformations and were inherited from a phenotypically normal balanced translocation carrier, it is likely that the extra copy of the triplicated 9 McFadden et al, 10,11 Baumer et al, 12 Daniel et al 13 and Kajii et al 14 Triploidy, trisomy and choice of active X BR Migeon et al segment was expressed. Direct duplications in males and females were also mapped but were not used for exclusions, as both copies are on the same chromosome and might function as one copy rather than two and might be subject to position effects.…”
Section: Inactivation Studiesmentioning
confidence: 99%
“…Perturbation of imprint balance drives several pathologies epitomized by female ovarian germ cell tumors (Linder et al 1975;Kajii and Ohama 1977;Surani et al 1984;Surti et al 1990;Devriendt 2005;Oosterhuis and Looijenga 2005;McFadden and Robinson 2006). TGCTs have been less explored as imprinting models, perhaps because they originate early on in the male germline and their imprint status is less established, with reports ranging from generally erased to relatively intact (Verkerk et al 1997;Looijenga et al 1998;Sievers et al 2005;Rijlaarsdam et al 2015).…”
mentioning
confidence: 99%
“…Other authors also found a predominance of paternal triploidy over maternal, but the cases examined were in the [11][12][13][14] th week of pregnancy [14]. On the other hand, McFadden et al (2006) reported higher incidence of digynic triploidy, but their series, the same as ours, evaluated early spontaneous abortions [15]. Since only early spontaneous abortions up to the 11 th week of gestation were included in our study, this could partially explain the predominance of digynic triploidies.…”
Section: Discussionmentioning
confidence: 54%